2007
DOI: 10.1634/stemcells.2006-0811
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Senile Osteoporosis in Normal Mice by Intra-Bone Marrow-Bone Marrow Transplantation from Osteoporosis-Prone Mice

Abstract: A P6 substrain of the senescence accelerated mouse (SAMP6) spontaneously develops osteoporosis early in life. These mice show the clinical signs of osteoporosis, such as elevated levels of urinary deoxypyridinoline (Dpd), decreased bone mineral density (BMD), and a significant loss of trabecular and cortical bone thickness at 12 months of age. Here, we describe the transfer of osteoporosis to a normal strain by the injection of bone marrow cells from SAMP6 donors directly into the bone marrow cavity (intrabone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…23 Interestingly, bone marrow transplantation from normal to recipient SAMP6 mice resulted in a significant increase in trabecular bone and BMD. [24][25][26] This finding confirms that the defect in SAMP6 mice originates in bone marrow and can be rescued by normal marrow.…”
Section: Senescence-accelerated Micesupporting
confidence: 73%
“…23 Interestingly, bone marrow transplantation from normal to recipient SAMP6 mice resulted in a significant increase in trabecular bone and BMD. [24][25][26] This finding confirms that the defect in SAMP6 mice originates in bone marrow and can be rescued by normal marrow.…”
Section: Senescence-accelerated Micesupporting
confidence: 73%
“…These cells were transduced with either vector control or sense Zfp467 containing constructs. Intra-tibial injection methods have been used successfully to study agerelated bone diseases including osteoporosis, and the ability of donor cells to proliferate and survive in recipient bone marrow following intra-tibial injections has been confirmed in previous studies (35,36). The presence of introduced calvarial cells was confirmed 7 days post-inoculation by Q-PCR for empty vector or transgenic Zfp467 transcripts (Fig.…”
Section: Increased Zfp467 Enhances Adipocyte Formation In Vivo-mentioning
confidence: 66%
“…However, some studies have demonstrated age-related changes in the concentration of osteoblast-active molecules such as IGF-I and TGF-b in the bone matrix (Bismar et al, 1999;Seck et al, 1999). Also, an osteoporotic phenotype was created in a normal healthy mouse by intramedullary injection of bone marrow cells obtained from the senescence-accelerated mouse prone 6 (SAMP6), a well-characterized model for accelerated aging, including an osteoporotic phenotype (Ueda et al, 2007). Owing to the limited engraftment of the transplanted cells, one explanation of these data could be a defective microenvironment in SAMP6 senescent and osteoporotic cells.…”
Section: Senescent Osteoblastic Cells Create a Defective Microenvironmentioning
confidence: 99%